Perbaikan Stabilitas Dinamik Sistem Tenaga Terintegrasi Pembangkit Listrik Tenaga Mikro Hidro dan Diesel Menggunakan PSS Berbasis ANFIS - I Made Ginarsa; I Made Ari Nrartha; Sultan Sultan; Agung Budi Muljono; Sabar Nababan (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2020)
Power generating units should be built closed to load centers according to electric power company regulation. These units are generally small in capacity, so that makes power transfer among inter- and outer-areas is easier to be done. This study aims to improve dynamic stability of a Micro Hydro Power Plant (MHPP) on perspective of 5% load increased in Diesel Power Plant (DPP). The DPP is equipped by an ANFIS-based Power System Stabilizer (PSS) in this scheme. Two inputs with Gauss2mf membership function (MF) type and 5-number of the each MF are used to implement the ANFIS model. Simulation results show that overshoot of MHPP power angle deviation is reduced to the values of 0.023, 0.0138 and 0.0132°, for the DPP without PSS, conventional and ANFIS PSS, respectively.  Also, reduction in setting time is achieved at times >6, 4.051 and 3.553 s. It is shown that the ANFIS PSS is more effective to enhance the dynamic stability compared to other PSS